ヘリ搭載型マイクロ波放射計を用いた南大洋・オホーツク海での海氷観測 - 田村, 岳史; 大島, 慶一郎; Jan, L. Lieser; 豊田, 威信; 舘山, 一孝; 野村, 大樹; 中田, 和輝; Alexander, D. Fraser; Peter, Jansen; Kym, Newbery; Robert, A. Massom; 牛尾, 収輝; et al. (2013)
Spatial distribution of thin sea ice thickness and its variability is a key to accurate estimation of surface albedo, oceanatmosphere heat-fluxes, and rates of ice production and salt-flux. For the validation and improvement of the thin ice thickness algorithm using the satellite passive microwave data, we have done in-situ observations in thin ice region in the Southern Ocean and the Sea of Okhotsk, using a helicopter-borne portable passive microwave radiometer same sensor as the satellite launched Advanced Microwave Scanning Radiometer-EOS (AMSR-E) and Advanced Microwave Scanning Radiometer-2 (AMSR-2). High-resolution helicopter-borne results show good agreement with low-resolution AMSR-E/AMSR-2 results, within the range of the standard deviation. In the Sea of Okhotsk experiment, the results derived from the helicopter-borne sensor are fitting to the past thin ice thickness algorithm. In the Southern Ocean experiment, the polarization ratio of 36 GHz vertical and horizontal temperatures in the Dalton Iceberg Tongue Polynya in October is estimated to be 0.137 in average. This value does not conflict with past in-situ observations, theoretical models, and thin ice thickness algorithms. We further found the microwave characteristics of fast versus pack ice, leading to the improvement for the fast ice detection algorithm. 第4回極域科学シンポジウム 個別セッション：[OM] 気水圏 11月15日（金） 統計数理研究所 ３階セミナー室１（D305） conference object